Prediction of successful vaginal birth after caesarean section based on Flamm and Geiger scoring system a prospective observational study - Sahu, Rajshree; Chaudhary, Naimaa; Sharma, Asha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The aim of this study was to evaluate the adequacy of Flamm and Geiger scoring system in prediction of successful vaginal birth after caesarean section. Methods: A prospective observational study was carried out on 75 pregnant women with previous one caesarean section in department of obstetrics and Gynecology, St Stephen’s hospital, New Delhi over a period of one year. Results: In the present study, out of 75 patients, 40% patients had successful VBAC and 60% patients had emergency LSCS. Among successful VBAC 70% patients had spontaneous vaginal delivery, while 23.3% patients had vacuum assisted and 6.7% had forceps assisted vaginal delivery. Most of the patients with total Flamm and Geiger score < 3 at the time of admission had emergency caesarean section while most of the patients with score >4 had successful VBAC. There were 53.3%, 75%, 85.7% and 100% probabilities of Successful VBAC with total score 4,5,6 and >8 respectively. Mean score for successful VBAC was 5±1.66and for emergency caesarean was 2.97±0.83. Conclusions: As total Flamm and Geiger score increases, a chance of successful VBAC increases. Application of Flamm and Geiger scoring gives fare judgment of successful vaginal birth in TOLAC and reduces the rate of failed trial leading to emergency caesarean section, thus improving outcome in a trial of labor.